The Influence of Meaningful Work and Work Environment on Organizational Commitment Through Work Engagement as a Moderator Variable in the Kuningan Regency Regional Apparatus - Erik Diyan Nurdiyansyah; Dikdik Harjadi; Lili Karmela (International Journal Labs, 2024)
Work engagement is a positive state, fulfillment, view of working conditions which is characterized by vigor, dedication, and absorption. Employees who have a high level of work engagement will show their best performance, this is because these employees enjoy the work they do. However, there are also employees who are less enthusiastic about preparing themselves and less enthusiastic about carrying out their work, but there are also employees who are still struggling with their work during break times and are willing to come home late at night or in other words find it difficult to escape from work. The aim of this research is to determine the role of work engagement in moderating the influence of meaningful work and the work environment on organizational commitment in regional apparatus Kamuning Kuningan Regency. This research uses a descriptive verification method with a quantitative approach. Primary data was collected using a questionnaire with a Likert Scale and 5 (five) answer choices, with a sample of 324 employees. The data obtained was then analyzed using the Partial Least Square (PLS) statistical method, which is a variance based Structural Equation Modeling (SEM) approach. In this research, PLS is used to analyze the entire construct formed with reflective indicators. The results of this research show that meaningful work has a significant positive effect on organizational commitment, the work environment has a significant positive effect on organizational commitment. Meanwhile, work engagement is able to act as a moderating variable on the influence of meaningful work and the work environment on organizational commitment.